2015
DOI: 10.1590/2236-8906-39/2014
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de bioestimulante composto de cinetina, ácido indolbutírico e ácido giberélico em epífitas, visando a restauração florestal

Abstract: -(Effect of the biostimulant compounded of kinetin, butyric acid, and gibberellic acid on epiphytes for forest restoration). The present study evaluated the effect of biostimulant (Cytokinin as kinetin 0.009%, Gibberellic acid 0.005%, and Indole-3-butyric acid 0.005%) on the development of three epiphyte species aiming their introduction on forest restoration management. Concentrations of 0, 4, 8, and 12 mL L -1 of bioestimulant Stimulate ® were applied by leaf spray on Vriesea carinata Wawra (Bromeliaceae), O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…The observed increase in the forage mass accumulation rate with doses higher than 1.8kg/ha BIOST.A can therefore be attributed to stimulation by the sprayed auxin. Previous studies evaluating the effects of exogenous auxin sources on other plant species also observed increased productivity (Cato, 2006;Silva et al, 2010;Silva et al, 2013b andLunelli et al, 2015).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The observed increase in the forage mass accumulation rate with doses higher than 1.8kg/ha BIOST.A can therefore be attributed to stimulation by the sprayed auxin. Previous studies evaluating the effects of exogenous auxin sources on other plant species also observed increased productivity (Cato, 2006;Silva et al, 2010;Silva et al, 2013b andLunelli et al, 2015).…”
Section: Discussionmentioning
confidence: 80%
“…Because their use recommendations are aimed at fruit and vegetable crops (Castro & Vieira, 2001;Cato, 2006;Silva et al2013a;Silva et al, 2013b;Lunelli et al, 2015), a lack of knowledge exists about the biostimulation effects of these products on tropical forage plants. In this context, plant biostimulants are therefore a promising alternative for forage production since, as with other crops, they could have beneficial effects on forage plants by stimulating forage mass production per unit of area, decreasing rest periods, and/or improving plant responses to fertilization.…”
Section: Introduction mentioning
confidence: 99%
“…Relocation -The plants of A. distichantha and W. cyathiformis utilized for the relocation showed an average of 19.61 and 13.65 leaves, respectively, and showed a good phytosanitary condition. The relocation was carried out in November 2015, during the highest rainfall period, as recommended by Lunelli et al (2015). For the relocation of bromeliads as epiphytes, plants were fixed on trees on their pitchforks or trunks regardless of the species, as also reported by Jasper et al (2005).…”
Section: Methodsmentioning
confidence: 99%
“…The factors associated with the individual morphological characteristics, which have probably determined the survival percentages, should also be considered since both species were in good phytosanitary conditions during their maintenance in the nursery. Lunelli et al (2015) observed that epiphytes have diverse responses when transplanted and recommend studying the species' biology to monitoring relocation.…”
Section: Bamentioning
confidence: 99%